2006
DOI: 10.1021/bi060305b
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-Bound Dimer Structure of a β-Hairpin Antimicrobial Peptide from Rotational-Echo Double-Resonance Solid-State NMR

Abstract: The intermolecular packing of a beta-hairpin antimicrobial peptide, PG-1, in lipid bilayers is determined using solid-state NMR distance measurements. Previous spin counting experiments showed that PG-1 associates as dimers in POPC bilayers; however, the detailed dimer structure was unknown. We have now measured several intermolecular 13C-19F, 1H-13C, and 15N-13C distances in site-specifically labeled PG-1 to constrain the structure of the intermolecular interface. The distances are measured using the rotation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
203
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(213 citation statements)
references
References 40 publications
(141 reference statements)
9
203
0
1
Order By: Relevance
“…In our hands, higher order AMPs also tend to be more cytotoxic, reflecting their increased interactions with mammalian membranes. B2088 retains its monomeric state in various media, which is in agreement with biophysical observations of other AMPs (51,63,79). The trend in designing AMPs toward higher covalent order might be limited by increased cytotoxicity and can be counteracted by designing lower order AMPs, maintaining high mobility in LPS and providing higher concentrations at the lipid surfaces of bacteria.…”
Section: Discussionsupporting
confidence: 87%
“…In our hands, higher order AMPs also tend to be more cytotoxic, reflecting their increased interactions with mammalian membranes. B2088 retains its monomeric state in various media, which is in agreement with biophysical observations of other AMPs (51,63,79). The trend in designing AMPs toward higher covalent order might be limited by increased cytotoxicity and can be counteracted by designing lower order AMPs, maintaining high mobility in LPS and providing higher concentrations at the lipid surfaces of bacteria.…”
Section: Discussionsupporting
confidence: 87%
“…In the anionic membrane, PG-1 contacts both the lipid headgroup and acyl chains and thus is well inserted. The peptide assembles into (NCCN) n multimers whose like-stranded interfaces are constrained not only by F-F distances but also by previously measured heteronuclear distances in POPC bilayers (20), which indicated parallel packed and hydrogen-bonded C strands. Such a hydrogen-bond stabilized (NCCN) n multimer strongly suggests the formation of a ␤-barrel.…”
Section: Discussionmentioning
confidence: 86%
“…This hypothesis is inconsistent with the current data. Instead, the PG-1 ␤-barrel has tight C strand interfaces, where the shortest intermolecular distance is 2.5 Å between Cys 15 CЈ and Cys 15 H N (20). Even the N strand interfaces, with fewer distance constraints so far, have a remarkably short Phg 7 -Phg 7 distance (6.5 Å) and a high percentage (75%) of dimerization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further ssNMR structural study of the MAX1 peptide, which has a very similar structure, showed that such peptides stack in an anti (head‐above‐tail) orientation 8d. Other amphipathic β‐hairpins have formed face‐to‐face dimers both in syn (head‐above‐head) and anti relative orientations, which can be affected by their environment 11. The phosphopeptide bilayer is comparable to that of amphiphilic peptide arrangements of KLVFF‐containing peptides, which form helical bilayer nanotapes that close to form nanotubes 12.…”
mentioning
confidence: 99%